Relationship between the perception of the work environment that the nursing staff has and the human care provided to the patient in the Maternal Intensive Care Unit from the National Maternal and Perinatal Institute, Lima - Espinoza de la Sota, Irene Beatriz (2019)
Objective: To determine the relationship between the perception of the work environment that has nurses andhuman care provided to the patient in Intensive Care Unit Maternity (MICU) of the National Maternal andPerinatal Institute. Methods: The study is not experimental, transversal and descriptive correlational design. Thepopulation consisted of 28 nurses working in the area of Maternal Intensive Care National Maternal PerinatalInstitute. For data collection was applied two instruments: a questionnaire to assess the perception of thework environment by considering four dimensions, and an observation guide for assessing human care; Bothinstruments were developed by the researcher. Statistical Rho Spearman correlation was used to establish therelationship between the variables. Results: The results show that there is no significant relationship betweenthe variables work environment and human care as tested Rho Spearman ρ = 0.239, and p = 0.220 value that isgreater than the value set α = 0.05, however, he found a implication significant correlation between the humandimension and care provided by the nurse. Conclusions: There is no significant correlation between the workenvironment perceived by the nurse and human care provided to the patient in the Intensive Care Unit Maternity(MICU) of the National Maternal and Perinatal Institute